Book Review: This Changes Everything: Capitalism Vs. The Climate. Issue 1 (March 2015) - Finn, John C.; Castree, Noel; Declet-Barreto, Juan; Johnson, Leigh; Larner, Wendy; Liverman, Diana; Watts, Michael; Finn, John C.
In Naomi Klein's latest book, This Changes Everything: Capitalism vs. the Climate (Simon & Schuster, 2014), the activist, journalist, and author lays out an argument that will probably be familiar to many readers of Human Geography . Carbon is not the problem, but rather a symptom of the real problem: global capitalism. The purpose of this Human Geography book review symposium is to give serious academic consideration to Klein's ideas, arguments, and visions of a carbon-free future. Thus in the pages that follow, six geographers—Noel Castree, Juan Declet-Barreto, Leigh Johnson, Wendy Larner, Diana Liverman, and Michael Watts—weigh in with their readings and critiques of Klein's book. Following these six reviews and concluding the symposium is the full text of the hour-long interview conducted by John Finn with Klein in late 2014.